2005
DOI: 10.4049/jimmunol.174.6.3484
|View full text |Cite
|
Sign up to set email alerts
|

The Protooncogene c-Maf Is an Essential Transcription Factor for IL-10 Gene Expression in Macrophages

Abstract: IL-10 is an important immunoregulatory factor. However, our understanding of IL-10 gene regulation remains very limited. In this study, following up on our previous novel finding that the protooncogene c-Maf of the basic leucine zipper family of transcription factors is expressed in monocytes and macrophages, we investigate the role of c-Maf in the transcriptional regulation of IL-10 and the underlying molecular mechanism in macrophages. c-Maf-null macrophages exhibit strongly impaired IL-10 protein production… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
199
2
5

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(218 citation statements)
references
References 61 publications
12
199
2
5
Order By: Relevance
“…Although we wished to determine IL-10 promoter activity 5 h after LPS stimulation, as was the case for IL-10 protein and mRNA measurements, luciferase levels were measured 8 h after LPS treatment, because shorter incubation times produced insufficient signal levels (data not shown). Similar to results reported in previous studies (6,11), LPS was found to elicit an ϳ10-fold increase in IL-10 promoter activity (Fig. 2C).…”
Section: The Stimulatory Effect Of Adenosine On Il-10 Production Is Nsupporting
confidence: 91%
See 1 more Smart Citation
“…Although we wished to determine IL-10 promoter activity 5 h after LPS stimulation, as was the case for IL-10 protein and mRNA measurements, luciferase levels were measured 8 h after LPS treatment, because shorter incubation times produced insufficient signal levels (data not shown). Similar to results reported in previous studies (6,11), LPS was found to elicit an ϳ10-fold increase in IL-10 promoter activity (Fig. 2C).…”
Section: The Stimulatory Effect Of Adenosine On Il-10 Production Is Nsupporting
confidence: 91%
“…Induction of IL-10 gene expression following LPS administration depends on a transcriptional process initiated by binding of the transcription factors Sp1 (6 -9), Sp3 (9), Stat3 (10), C/EBP␤ and ␥ (9), and c-Maf (11) to the IL-10 promoter. cAMP-elevating agents trigger IL-10 promoter activity and IL-10 secretion in human monocytic cells, secondary to an enhanced binding of CREB, as well as C/EBP␣ and ␤, to the IL-10 promoter (12).…”
mentioning
confidence: 99%
“…The transcription factor cMaf is induced by IL-10 and acts to up-regulate IL-10 production and to inhibit IL-12p40 and IL-12p35 expression (49). Most recently the presence of c-Maf was shown to be essential for optimal IL-10 production by macrophages (50). Interestingly the addition of IL-4 in this system resulted in enhanced c-Maf and IL-10 expression (50).…”
Section: Discussionmentioning
confidence: 97%
“…Rodriguez and colleagues have recently shown that c-Maf is also the putative target of miR-155 (33), and ectopically expressed c-Maf is sufficient to trigger IL-10 production by immune cells (39,40). In addition to miR-155, several other miRNAs, including miR-146 and miR-150 have been shown to play pivotal roles in the inflammatory responses and hematopoiesis of immune cells (21,41).…”
Section: Discussionmentioning
confidence: 99%